2022
DOI: 10.3389/fgene.2022.875182
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of a Targeted Next Generation Sequencing Gene Panel in Providing Molecular Diagnosis to Patients With a Broad Spectrum of Neurodevelopmental Disorders

Abstract: Background: Neurodevelopmental disorders comprise a clinically and genetically heterogeneous group of conditions that affect 2%–5% of children and represents a public health challenge due to complexity of the etiology. Only few patients with unexplained syndromic and non-syndromic NDDs receive a diagnosis through first-tier genetic tests as array-CGH and the search for FMR1 CGG expansion. The aim of this study was to evaluate the clinical performance of a targeted next-generation sequencing (NGS) gene panel as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…At one end, we noticed a misexpression, usually an under-expression, of at least 2 of 4 glucose transporters in every patient. This finding is consistent with studies describing a link between neurodevelopmental disorders, including ASD, and gene anomalies, namely variants or deletions (Mellone et al 2022; Mir et al 2022; López-Rivera et al 2020; Lee, Smith, and Paciorkowski 2015; Redin et al 2014; Srour et al 2017). However, at the other end, no previous study reported an association between ASD and molecular anomalies for SLC16A9 and SLC16A14, two pyruvate transporters.…”
Section: Discussionsupporting
confidence: 92%
“…At one end, we noticed a misexpression, usually an under-expression, of at least 2 of 4 glucose transporters in every patient. This finding is consistent with studies describing a link between neurodevelopmental disorders, including ASD, and gene anomalies, namely variants or deletions (Mellone et al 2022; Mir et al 2022; López-Rivera et al 2020; Lee, Smith, and Paciorkowski 2015; Redin et al 2014; Srour et al 2017). However, at the other end, no previous study reported an association between ASD and molecular anomalies for SLC16A9 and SLC16A14, two pyruvate transporters.…”
Section: Discussionsupporting
confidence: 92%
“…Next generation sequencing (NGS) can detect underlying pathogenic gene variants. It has been demonstrated that NGS, analyzing a large number of genes simultaneously, proves to be highly efficient and cost-effective ( 72 , 73 ). By implementation of novel analysis tools, CNVs can also be detected by NGS.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the joint detection of CNVs and SNVs (single nucleotide variants) should be performed in newborns with complex phenotypes, as it might disclose the co-presence of multiple genetic factors. Currently, such patients are diagnosed through a step by step approach, including aCGH [ 27 ], targeted gene panels [ 28 ], exome sequencing, and in some accurately selected cases Whole Genome Sequencing (WGS), which is still expensive and requires specialized bioinformatic skills. In the future, with the improvement of bioinformatic tools, training of specialized personnel, and cost reductions, the introduction of routine diagnostics of WGS, detecting any type of genetic alteration, will greatly improve the management of these patients.…”
Section: Discussionmentioning
confidence: 99%